Innovations in Vesicular Drug Delivery: The Proniosomal Approach for Enhanced Therapeutic Efficacy - Saritha Medapati; Satya Prakash Panda; Krishna Mannem; Latha Kukati (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
Novel drug delivery systems have made great progress in the field of nanotechnology. This review focuses on different aspects of proniosomes such as preparation, characterization, in vitro drug release, entrapment efficiency, applications in the present scenario in the market and future trends. In the development of new dosage forms, drug delivery using nanotechnology is playing a vital role. Vesicular drug delivery systems have gained wide attention in the field of nanotechnology, such as niosomes, liposomes and proniosomes. Among the vesicular carriers, proniosomes are superior. Proniosomes are water-soluble carrier particles that are coated with surfactant so these are dry formulations. They are rehydrated to use on agitation in hot aqueous media within minutes to form niosomal dispersion immediately. Both hydrophilic and lipophilic drugs can be incorporated into these proteasomes. The physical stability problems of niosomes like aggregation, fusion and leaking are minimized in proniosomes, routes, such as oral, parenteral, dermal and transdermal, ocular, oral mucosal, vaginal, pulmonary, and intranasal. In the treatment of hypertension, Proniosomes are used as carriers for the transdermal delivery of captopril. Proniosomes are also used for the delivery of levonorgestrel the emergency contraceptive and many more. Proniosomes prolong the existence of the drug in the systemic circulation and finally reduce toxicity. Proniosomes are an effective tool for targeting of drugs and have the potential to provide better treatment than conventional drug delivery system.